Modeling national accounts sub-aggregates: An application of non-linear error correction - Adusei Jumah; Robert M. Kunst (Institute for Advanced Studies (IHS), 2004)
Many macroeconometric models depict situations where the shares of the major demand aggregates in output are stable over time. The joint dynamic behavior of the considered demand aggregate and output may thus be approximated by a cointegrated vector autoregression. However, the shares of many demand sub-aggregates in output are rather mobile and changing over time. In order to simultaneously capture the flexibility of the shares of the sub-aggregates and the long-run constancy of the share of the total aggregate, we consider trivariate systems of two macroeconomic sub-aggregates and output with errorcorrection terms that are non-linear functions of the original variables. The merits of the models are evaluated by means of several forecasting experiments.
Keywords: C32; C53; E27; 330; macroeconomic accounts; great ratios; non-linear error correction; forecasting; Volkswirtschaftliche Gesamtrechnung; Konjunkturprognose; Prognoseverfahren; Unit Root Test; Schätzung; Österreich; Frankreich; Großbritannien; Fehlerkorrekturmodell; Nichtlineares Verfahren